Enhancing Business Research Method Course Outcomes: The Role of Integrated PBL and PjBL Models - Untung Lasiyono; Wira Yudha Alam; Siti Istikhoroh (Journal of Innovation in Educational and Cultural Research, 2024)
This research evaluates the efficacy of integrating Problem-Based Learning (PBL) and Project-Based Learning (PjBL) in business research methods at a university that provides educational and non-educational programs in Surabaya, Indonesia, aligning with national educational standards. The study aims to assess the impact of blended PBL and PjBL models on student performance, aiming for improved comprehension and application of research methods concepts. A quantitative approach was employed, sequentially applying PBL and PjBL within the curriculum. The 2022 Accounting Study Program cohort was sampled via random selection. Student-prepared research proposals were evaluated, and data were analyzed using multiple linear regression. The integrated PBL and PjBL significantly correlate with enhanced academic performance in business research methods, suggesting improved understanding and application of concepts. This study demonstrates the effectiveness of integrating PBL and PjBL to achieve competency-based educational goals in business research methods. By aligning with national standards, this approach enhances learning experiences and provides valuable insights for similar contexts.